Perfil sociodemográfico y clínico de las personas atendidas en el programa "Código Riesgo Suicidio de Cataluña". - Gayete, Sílvia; Giné, Anna; Marcos, Sandra; Vidal, Maria Adela; Ventura, Cristina; Ochoa, Susana (Actas Espanolas de Psiquiatria)
Introduction. Suicide is an issue with a great impact on public health. For this reason, the Catalonia Suicide Risk Code (CSRC) protocol was developed in 2015. The aim of this paper is to examine the sociodemographic and clinical profile of patients for whom this protocol was activated between 2016 and 2017 in our reference population. Methodology. Retrospective descriptive study of recorded data on Suicide Risk Code of our population attended (n=246 in 2016 and n=391 in 2017) in the mental health outpatient services of the Parc Sanitari Sant Joan de Déu being attended previously in the emergency services of any of the hospitals of reference. Results. The most prevalent profile in both 2016 and 2017 was woman between 40 and 55 years of age with stressful life events. The most prevalent method used was substance abuse. Conclusions. The data suggest that the health care task should be adjusted to the highest risk profile observed in our reference population, considering stressful live events as significant risk factors which should be taken into account.